2021
DOI: 10.14245/ns.2040722.361
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methods of Necroptosis Inhibition for Spinal Cord Injury Using Translational Research to Limit Secondary Injury and Enhance Endogenous Repair and Regeneration

Abstract: Spinal cord injuries (SCI) pose an immense challenge from a clinical perspective as current treatments and interventions have been found to provide marginal improvements in clinical outcome (with varying degrees of success) particularly in areas of motor and autonomic function.In this review, the pathogenesis of SCI will be described, particularly as it relates to the necroptotic pathway which has been implicated in limiting recovery of SCI via its roles in neuronal cell death, glial scarring, inflammation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Mechanistically, the primary insult triggers a series of molecular and cellular cytotoxic events that, in concert, cause further nervous tissue damage and degeneration [ 1 , 2 ]. Protecting nervous tissue from secondary damage is an important early line of defense to limit the devastating consequences of SCI [ 42 ]. We found that MSC and NHC both have neuroprotective effects that limit injury expansion in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the primary insult triggers a series of molecular and cellular cytotoxic events that, in concert, cause further nervous tissue damage and degeneration [ 1 , 2 ]. Protecting nervous tissue from secondary damage is an important early line of defense to limit the devastating consequences of SCI [ 42 ]. We found that MSC and NHC both have neuroprotective effects that limit injury expansion in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…91 The process is dependent on receptor-interacting serine/threonine kinase 1 and 3 and studies have shown that it may be one of the primary forms of cell death following trau-matic SCI. 91 Inhibition of this pathway is suspected to attenuate secondary damage and minimize cell death. 92 Autologous omental transplantation has been proposed as a method to introduce blood-and lymph-rich tissue to injured spinal cord tissue.…”
Section: Future Perspectivesmentioning
confidence: 99%
“… 8 9 10 11 Disruption of spinal cord blood vessels induces hemorrhage and ischemia at the SCI site. 12 13 14 In addition, excessive activated chemicals, such as the excitatory neurotransmitters glutamate or aspartate, cause damage to neurons, astrocytes, and oligodendrocytes. As a result, damage to oligodendrocytes leads to axonal demyelination, which impairs nervous system plasticity.…”
Section: Introductionmentioning
confidence: 99%